2014
DOI: 10.1038/srep06527
|View full text |Cite
|
Sign up to set email alerts
|

Reduced miR-3127-5p expression promotes NSCLC proliferation/invasion and contributes to dasatinib sensitivity via the c-Abl/Ras/ERK pathway

Abstract: miR-3127-5p is a primate-specific miRNA which is down-regulated in recurrent NSCLC tissue vs. matched primary tumor tissue (N = 15) and in tumor tissue vs. normal lung tissue (N = 177). Reduced miR-3127-5p expression is associated with a higher Ki-67 proliferation index and unfavorable prognosis in NSCLC. Overexpression of miR-3127-5p significantly reduced NSCLC cells proliferation, migration, and motility in vitro and in vivo. The oncogene ABL1 was a direct miR-3127-5p target, and miR-3127-5p regulated the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…We also verified the consistent relationship between the expressions of miR‐3127‐5p and EMT markers in vivo. However, it should be pointed out that since we observed more lung metastases in miR‐3127‐5p‐inhibited xenografts in our previously reported paper, we just investigated the effects of miR‐3127‐5p on EMT by subcutaneous tumor formation in this study. Moreover, we found that downregulation of miR‐3127‐5p resulted in decreased expression of Vimentin in the lung metastatic tumors, which may be beneficial for tumor colonization.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…We also verified the consistent relationship between the expressions of miR‐3127‐5p and EMT markers in vivo. However, it should be pointed out that since we observed more lung metastases in miR‐3127‐5p‐inhibited xenografts in our previously reported paper, we just investigated the effects of miR‐3127‐5p on EMT by subcutaneous tumor formation in this study. Moreover, we found that downregulation of miR‐3127‐5p resulted in decreased expression of Vimentin in the lung metastatic tumors, which may be beneficial for tumor colonization.…”
Section: Discussionmentioning
confidence: 94%
“…Since the in vitro experiments revealed that downregulation of miR‐3127‐5p promotes EMT and cell invasion in NSCLC cell lines, we next asked whether downregulation of miR‐3127‐5p could promote EMT in vivo. In view of the phenomenon that more lung metastases were observed in miR‐3127‐5p‐inhibited xenografts in our previously reported paper, we just investigated the effects of miR‐3127‐5p on EMT by subcutaneous tumor formation in this study. The tumor growth curve indicated that tumors in miR‐3127‐5p inhibition group grew more quickly than tumors in the negative control group (Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with these data, downregulation of microRNAs (miRNAs; miRs) that inhibit ABL1/2 expression, also drives disease development. ABL1 is a direct target of miR-3127–5p, which is downregulated in non-small cell lung cancer (NSCLC) patients and is associated with a poor prognosis [44]; miR-3127–5p and ABL1 expression is inversely correlated in patient samples; and loss of miR-3127–5p correlates with dasatinib sensitivity in NSCLC lines lacking KRAS mutations [44]. Likewise, miR-125a-5p, which is downregulated in cervical cancer cell lines and primary tumors, directly targets ABL2, and ABL2 knockdown parallels the effects of miR-212a-5p overexpression on proliferation/migration [45].…”
Section: Mechanism Of Abl1/abl2 Activation In Solid Tumorsmentioning
confidence: 99%